In‐situ Mass Balance Estimates Offshore Costa Rica. (17th February 2021) - Edwards, J.; Kluenser, Jared; Silver, Eli; Lauer, Rachel; Bangs, Nathan; Boston, Brian
Abstract: The Costa Rican convergent margin has been considered a type erosive margin, with erosional models suggesting average losses up to −153 km 3 /km/m.y. However, three‐dimensional (3D) seismic reflection and Integrated Ocean Drilling Program data collected offshore the Osa Peninsula images accretionary structures and vertical motions that conflict with the forearc basal erosion model. Here we integrate such data to do an in‐situ accounting of material transfer at the plate boundary across the outermost 10 km of the forearc, characterized by active and inactive megathrusts. Our in‐situ budget finds an approximate balance between sediment recycling via accretion and underplating, 0.7–2.3 km 3 /km/m.y., and basal erosion, 0.7 km 3 /km/m.y., while subducting sediment volumes, 7.8 km 3 /km/m.y., greatly outpace either material transfer volumes. These budget results differ significantly from published estimates based on simple proxies of trench axis deflection and slope subsidence. These budget results are the summation of thin incoming hemipelagic sediments that variably accrete along the deformation front, underplating of hemipelagic sediments on the upthrown‐side and basal erosion on the downthrown‐side of active plate bending faulting landward of the trench axis, and sediment subduction primarily composed of pelagic sediments. Plain Language Summary: Subduction zones, where tectonic plates meet and dive under or over their neighbors, are environments of material exchange, where sediments and rocks are given, or taken away. Either of the converging plates, the one going under or over, can theoretically add or remove material depending on a number of conditions. Understanding what those conditions are and how much is added or removed is challenging, given these interactions occur offshore and deep in the earth. For decades, marine geoscientists have used proxies to estimate how much material is exchanged at subduction zones around the world. For the first time, new 3D imaging data allows us to directly estimate material exchange at a subduction zone. Using these data, we estimate the material exchange for a ∼10 km wide and ∼10 km long section of the subduction zone offshore Costa Rica, which has been considered an eroding continent. These new data show that for the footprint studied, the Costa Rican continent is not shrinking, but is balanced to slowly growing. Key Points: An in‐situ mass balance of 100 km 2 of the outermost forearc offshore Costa Rica finds a balanced to slowly growing upper plate Thin subducting sediments variably accrete at the deformation front and underplate along the upthrown‐side of active plate‐bending faults Basal erosion is co‐located with the downthrown‐side of both seaward and landward‐dipping active plate‐bending faults